Pain through the perspective of art and creativity: insights from the Unmasking Pain project - Johnson, Mark I.; Chazot, Paul; Cole, Frances; Cruickshank, Rosemary; Fuller, Dawn; Keyse, Charlotte; Singh, Balbir; Strickson, Adam J.; Tabasam, Ghazala; Tregidden, Emma; Thompson, Kate; Woodall, James (Frontiers in Pain Research, 2023)
People struggle to tell their story of living with pain and when they do it is articulated in a way that may not be understood, heard or taken seriously. Unmasking Pain is an artist-led project that explored creative approaches to tell stories of life with pain. The project was led by a dance theatre company that specialises in storytelling and emotional experiences for players and audiences. The project involved artists and people living with ongoing pain co-creating activities and environments to curiously explore “oneself”, through imagination and creative expression. This article discusses insights and perspectives emerging from the project. The project revealed the power of art to make-sense of oneself with or without pain, and how art facilitates expression of complex inner experience and personal stories. People described Unmasking Pain as “explorative joy despite pain”, and “a new set of rules” that contrasts with those experienced during clinical encounters. We discuss how art has the potential to improve clinical encounters and promote health and well-being, and whether artist-led activities are an intervention, therapy, or something else. Pain rehabilitation specialists from the project described Unmasking Pain as “freeing-up thinking”, allowing conceptual thought beyond the biopsychosocial model of pain. We conclude that art has the potential to shift people living with pain from “I can't do, I am not willing to do it” to “Perhaps I can, I'll give it a go, I enjoyed”.